Achromatic Dielectric Metasurface with Linear Phase Gradient in the Terahertz Domain. Issue 2 (25th November 2020) - Jia, Ridong; Gao, Yufei; Xu, Quan; Feng, Xi; Wang, Qingwei; Gu, Jianqiang; Tian, Zhen; Ouyang, Chunmei; Han, Jiaguang; Zhang, Weili
Abstract: The notion of metasurface has inspired the innovation of various functional devices in the terahertz band, but the intrisinc dispersion restricts their application in broadband scenarios. Here, two terahertz achromatic linear‐phase‐gradient metasurface devices are demonstrated, which are a beam deflector and a beam splitter, respectively. The phase and dispersion of the metasurfaces are simultaneously engineered by changing the geometric parameters of the unit cells made of silicon gratings and pillars. The simulated and experimental results demonstrate the achromatic feasibility of the beam deflector from 0.6 to 1.2 THz and of the beam splitter from 0.6 to 1.1 THz. The transmittances and the splitting ratios of the achromatic beam splitter are also analyzed. The metasurface based achromatic beam deflector and splitter presented here not only enrich the terahertz functional devices, but the methods and structures may also promote the research of broadband terahertz metasurfaces. Abstract : Achromatic dielectric metasurface devices with linear phase gradient are theoretically analyzed and experimentally verified. Taking use of the subwavelength pillars and gratings structures fabricated by deep reactive ion etching (DRIE) on the silicon substrate, the achromatic beam steering and splitting are achieved in a broad terahertz bandwidth. The results presented here will promote the researches of achromatic terahertz devices.